2023
DOI: 10.1038/s41598-023-36747-4
|View full text |Cite
|
Sign up to set email alerts
|

A sub 1 GHz ultra miniaturized folded dipole patch antenna for biomedical applications

Abstract: A miniaturized folded dipole patch antenna (FDPA) design for biomedical applications operating at sub 1 GHz (434 MHz) band is presented. Antenna is fabricated on FR-4 substrate material having dimensions of 16.40 mm $$\times$$ × 8.60 mm $$\times$$ × 1.52 mm (0.023$$\lambda$$ λ $$\times$$ × 0.012$$\lambda$$ λ $$\times$$ × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Patch 2 has a length of 30 mm and a width of 30 mm. Using a single varactor in an antenna reconfigurable system offers several benefits [17]. Firstly, it simplifies the overall design by reducing the number of components required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patch 2 has a length of 30 mm and a width of 30 mm. Using a single varactor in an antenna reconfigurable system offers several benefits [17]. Firstly, it simplifies the overall design by reducing the number of components required.…”
Section: Methodsmentioning
confidence: 99%
“…In [17], a miniaturized folded dipole patch antenna design for biomedical application which operate at 1 GHz, the antenna side was reduce by 835 with lumped inductor places at the centre patch of the radiating which makes it suitable for hyperthermia, the proposed give an impendent band with 6 MHz. Several studies have demonstrated the potential of microwave hyperthermia in various cancer types, including breast cancer, head and neck cancer, and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%